Peran Etika Profesi Hukum sebagai Upaya Penegakan Hukum - Aisyah Putri Syam; Melza Mutiara Putri Mahrus; Teti Marlina Tarigan (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
The principle of the rule of law in the life of society and the state demands the role of the advocate as a free, independent and responsible profession in legal aid in the context of enforcing criminal law, in addition to the judiciary and law enforcement agencies. as the Police and Attorney General. Through the legal services provided, Advocates carry out their professional duties for the sake of upholding justice based on the law for the benefit of justice seekers, including efforts to empower the community to realize their basic rights before the law. Advocates as an element of law enforcement in criminal justice are one of the pillars in upholding the rule of law and human rights. Guarantee of equality before the law Keywords: Role, Professional Ethics, Law Enforcement.